Why do educated mothers matter? A model of parental help - Luciano Canova; Alessandro Vaglio (Kiel Institute for the World Economy (IfW), 2010)
This paper investigates the role performed by mothers in affecting their childrens' performance at school. The article develops firstly a theoretical model in which household (parent-child pair) is treated as an individual, whose utility depends both on the performance at school of the student and on consumption. The model focuses on the different possibilities through which help of mothers may affect pupil's performance both in terms of time devoted to supervision and spillover effects. Empirical evidence then, using PISA 2006 and focusing on Italian case, shows that education of mothers is an issue when interacted with her occupational status. Highly educated mothers have a positive impact on students' score only when they are highly qualified in the job market.
Keywords: J12; J21; J24; 330; education; PISA; quantile regressions; parental help; Bildungsniveau; Kinder; Mütter; Hochqualifizierte Arbeitskräfte; Frauenbildung; Schätzung; Italien